2011
DOI: 10.3390/ijms12085261
|View full text |Cite
|
Sign up to set email alerts
|

FK506-Binding Protein 22 from a Psychrophilic Bacterium, a Cold Shock-Inducible Peptidyl Prolyl Isomerase with the Ability to Assist in Protein Folding

Abstract: Adaptation of microorganisms to low temperatures remains to be fully elucidated. It has been previously reported that peptidyl prolyl cis-trans isomerases (PPIases) are involved in cold adaptation of various microorganisms whether they are hyperthermophiles, mesophiles or phsycrophiles. The rate of cis-trans isomerization at low temperatures is much slower than that at higher temperatures and may cause problems in protein folding. However, the mechanisms by which PPIases are involved in cold adaptation remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…However, unknown protein 18 and unnamed protein product could not be identified, probably these are not yet reported. PPIases identified in this study are ubiquitous proteins, mediating protein folding in cold stress (Budiman et al, 2011). Additionally, ROC4 (only cyclophilin in the stroma of the chloroplast) is shown to have PPIases activity and is involved in the repair of photo-damaged PSII in A. thaliana (Cai et al, 2008).…”
Section: Discussionmentioning
confidence: 85%
“…However, unknown protein 18 and unnamed protein product could not be identified, probably these are not yet reported. PPIases identified in this study are ubiquitous proteins, mediating protein folding in cold stress (Budiman et al, 2011). Additionally, ROC4 (only cyclophilin in the stroma of the chloroplast) is shown to have PPIases activity and is involved in the repair of photo-damaged PSII in A. thaliana (Cai et al, 2008).…”
Section: Discussionmentioning
confidence: 85%
“…Different members of cyclophilin subfamily were directly linked to multiple stresses. In this sense, Budiman et al ( 2011 ) proposed that foldase and chaperone activities of PPIases are the main requirements with which to overcome the cold-stress problem in microorganisms caused by protein folding.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the rate of cis/trans proline isomerization at low temperature is much slower than at higher temperatures, and consequently, folding of cis proline-containing proteins is the rate-limiting step for bacterial growth in cold environments (46). Thus, it was interesting to determine if the Brucella ⌬cypAB mutant has a reduced ability to grow at lower temperatures.…”
Section: Resultsmentioning
confidence: 99%